Seronegative Arthritis and Whipple Disease: Risk of Misdiagnosis in the Era of Biologic Agents - Luca Quartuccio; Ivan Giovannini; Stefano Pizzolitto; Maurizio Scarpa; Salvatore De Vita (Case Reports in Rheumatology)
We report 2 cases of Whipple disease (WD), previously diagnosed as seronegative polyarthritis and treated for several years with immunosuppressive agents, accordingly. Both cases had been treated over years with cDMARDs and bDMARDs. The first patient was a 48-year-old male, who developed a life-threatening disease characterized by fever, significant weight loss, and bloody diarrhoea, supported with RBC transfusions. The second patient was a 55-year-old man, presenting with arthritis, fever, serositis, lymphadenopathy, thoracic rash, and systemic inflammation; at the beginning he was diagnosed as adult onset Still’s disease. He was treated with steroids and antitumour necrosis factor agents, but showed no improvement. Both patients were eventually treated with antimicrobial therapy for WD with dramatic improvement and no clinical relapse in 6 months. This paper reviews the literature on WD mimicking chronic inflammatory arthritis. WD may lead to chronic seronegative arthritis that might often be misrecognized. Importantly, patients treated with bDMARDs and glucocorticoids might develop a life-threatening disease. Therefore, WD should be suspected and excluded in patients showing resistance or frequent recurrence of chronic arthritis, if seronegative, under treatment with bDMARDs, especially in the presence of new, unexpected sign and/or symptoms.